Chronic non-cancer pain management in primary care - Tasleem Ras (South African Family Practice, 2020)
Chronic non-cancer pain is a common, often undiagnosed condition in primary care across the world, with prevalence rates between 20% and 40%. To effectively address this problem, the primary care practitioner needs to have an organised, comprehensive approach to diagnosing and managing these patients within a biopsychosocial framework, in collaboration with members of the interdisciplinary team. The aim of this article is to provide the primary care practitioner with up to date information on the management of chronic pain. A case study is introduced to raise awareness of some of the complexities of dealing with the problem. A series of key questions are raised that address the various levels of complexity. Current evidence is used to guide the reader through these questions, covering a wide area of pain research as it pertains to primary care. The article concludes with five practice points that link the literature to clinical practice.